Development and binding characteristics of phosphonate inhibitors of SplA protease from Staphylococcus aureus. (24th December 2013) - Burchacka, Ewa; Zdzalik, Michal; Niemczyk, Justyna‐Stec; Pustelny, Katarzyna; Popowicz, Grzegorz; Wladyka, Benedykt; Dubin, Adam; Potempa, Jan; Sienczyk, Marcin; Dubin, Grzegorz; Oleksyszyn, Jozef
Abstract: Staphylococcus aureus is responsible for a variety of human infections, including life‐threatening, systemic conditions. Secreted proteome, including a range of proteases, constitutes the major virulence factor of the bacterium. However, the functions of individual enzymes, in particular SplA protease, remain poorly characterized. Here, we report development of specific inhibitors of SplA protease. The design, synthesis, and activity of a series of α‐aminoalkylphosphonate diaryl esters and their peptidyl derivatives are described. Potent inhibitors of SplA are reported, which may facilitate future investigation of physiological function of the protease. The binding modes of the high‐affinity compounds Cbz‐Phe P ‐(OC6 H4 −4‐SO2 CH3 )2 and Suc‐Val‐Pro‐Phe P ‐(OC6 H5 )2 are revealed by high‐resolution crystal structures of complexes with the protease. Surprisingly, the binding mode of both compounds deviates from previously characterized canonical interaction of α‐aminoalkylphosphonate peptidyl derivatives and family S1 serine proteases. Abstract : Interactive Figure 2 | PDB Code(s):4mvn ;3ufa